Biosynthesis of β-caryophyllene, a novel terpene-based high-density biofuel precursor, using engineered Escherichia coli. (December 2016) - Yang, Jianming; Li, Zhengfeng; Guo, Lizhong; Du, Juan; Bae, Hyeun-Jong
Abstract: β-caryophyllene is a common sesquiterpene compound currently being studied as a promising precursor for the production of high-density fuels. Acute demand for high-density fuels has provided the impetus to pursue biosynthetic methods to produce β-caryophyllene from reproducible sources. In this study, we produced β-caryophyllene by assembling a biosynthetic pathway in an engineered Escherichia coli strain of which phosphoglucose isomerase gene has been deleted. The 1- deoxy-d -xylulose 5-phosphate (DXP) or heterologous mevalonate (MVA) pathways were employed. Meanwhile, geranyl diphosphate synthase, glucose-6-phosphate dehydrogenase and β-caryophyllene synthase genes were co-overexpressed in the above strain. The final genetically modified strain, YJM59, produced 220 ± 6 mg/L of β-caryophyllene in flask culture. We also evaluated the use of fed-batch fermentation for the production of β-caryophyllene. After induction for 60 h, the YJM59 strain produced β-caryophyllene at a concentration of 1520 mg/L. The volumetric production fermented in the aerobic fed-batch was 0.34 mg/(L·h·OD600 ) and the conversion efficiency of glucose to β-caryophyllene (gram to gram) was 1.69%. Our results are the first successful attempt to produce β-caryophyllene using E. coli BL21(DE3), and provide a new strategy that is green and sustainable for the production of β-caryophyllene. Highlights: Construct a novel efficient metabolic pathway for the β-caryophyllene production. The strain YJM59 could accumulate β-caryophyllene up to 1.52 g/L under the fed-batch fermentation conditions. Our results provide a new strategy that is green and sustainable for β-caryophyllene production using Escherichia coli .